(untitled) (American Journal of Interdisciplinary Research and Development, 2023)
The article examines the role and importance of foreign investment in the socio-economic development of the country, studied international experience in attracting foreign investment into the national economy, and considered conclusions, proposals and recommendations based on international experience.